THE EFFECT OF Fe-ENRICH PHASE ON THE PITTING CORROSION RESISTANCE OF Al ALLOY IN VARIOUS NEUTRAL SODIUM CHLORIDE SOLUTIONS - Gadang Priyotomo; I Nyoman Gede Putrayasa Astawa (International Journal of Science and Engineering, 2014)
The pitting corrosion of 5052 alloy was investigated as function of chloride concentrations by using an electrochemical method, scanning electron microscope and energy dispersive X-Ray spectroscopy in neutral sodium chloride solutions at 293 K.  The pitting corrosion of pure Al was also investigated under the same experimental condition for the comparison. The pitting potential obtained for 5052 alloy and pure Al decreased with increasing chloride concentration.  The pitting potential of pure Al is higher than that of 5052 alloy where pitting resistance of pure Al is better than that 5052 alloy.  The linear equation implies that certain pitting potential becomes a relevant parameter for predicting certain chloride ion concentration.  The synergic role of chloride ion and a localized galvanic corrosion between aluminium metal and iron-containing constituent contribute the process of pitting for 5052 alloy.